2010
DOI: 10.4238/vol9-4gmr919
|View full text |Cite
|
Sign up to set email alerts
|

Genome elimination during microsporogenesis in two pentaploid accessions of Brachiaria decumbens (Poaceae)

Abstract: ABSTRACT. Polyploidy is a prominent and significant force in plant evolution, taking place since ancient times and continuing until today. Recent cytogenetic studies in the genus Brachiaria using germplasm collected from wild African savannas in the 1980s revealed that most species and accessions within species are polyploid. Diploid, tetraploid, and pentaploid accessions have been found. We found asynchronous meiosis during microsporogenesis, followed by genome elimination, in two pentaploid (2n = 5x = 45) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…This may indicate that the abnormalities were not sufficiently severe to produce infertility. Similar results were reported for B. decumbens accessions which had apparently normal pollen but in which 100% of the tetrads had micronuclei or were fragmented into polyads (Ricci et al, 2010).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This may indicate that the abnormalities were not sufficiently severe to produce infertility. Similar results were reported for B. decumbens accessions which had apparently normal pollen but in which 100% of the tetrads had micronuclei or were fragmented into polyads (Ricci et al, 2010).…”
Section: Resultssupporting
confidence: 76%
“…In Brachiaria, the various meiotic abnormalities observed in cytogenetic analyses compromise normal chromosome behavior and lead to the formation of infertile gametes (Risso-Pascotto et al, 2005;Mendes-Bonato et al, 2002Fuzinatto et al, 2007;Felismino et al, 2008, Ricci et al, 2010Souza-Kaneshima et al, 2010;Pagliarini et al, 2012a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Griseb., which is presently merged (Shirasuna, 2012) with the circumscription of Urochloa P. Beauv. (Ricci et al, 2010). Several polyploids were formed in the past by genome duplication events occurring millions of years ago (paleopolyploids), but according to Adams and Wendel (2005), polyploidy is an active and ongoing process; the meiotic behavior of the P. conspersum accessions analyzed here reinforces this proposition.…”
Section: Asynapsis and Hybridizationsupporting
confidence: 60%
“…Such meiotic behavior is typical of recently formed natural hybrids resulting from parental genomes with dissimilar meiotic rhythms. This phenomenon has previously been found in 1 accession of P. subciliatum Chase (Adamowski et al, 1998), has been reported several times in species of Brachiaria, and is presently accepted (Shirasuna, 2012) within the circumscription of Urochloa (Risso-Pascotto et al, 2004;Mendes-Bonato et al, 2006;Boldrini et al, 2009Boldrini et al, , 2010Ricci et al, 2010). Although several polyploids were formed as a result of genome duplication events occurring several millions of years ago, Wendel and Doyle (2005) consider it an active and ongoing process, termed paleopolyploidization; the meiotic behavior of the P. jesuiticum accessions reported here reinforces this view.…”
Section: Meiotic Behavior and Evidence Of Recent Natural Hybridizationmentioning
confidence: 86%